Democratic and participatory management: A need in state public schools in the headquarters of the Municipality of Alto Alegre – Roraima – Brazil (Research, Society and Development, 2024)
This article aimed to analyze the importance of democratic and participatory management that enables the principles of citizenship in the school context of State Public Schools based in the Municipality of Alto Alegre, Roraima, Brazil. Identifying its contribution as a relevant and significant proposal and strategy in the teaching and learning process. The organization, management, physical structure and materials guarantee the teaching and learning process, as well as quality teaching and compliance with the school calendar. In democratic management, there is a need to nullify the centralization of decision-making by the manager in the school community. It provides a view of school management, highlighting relevant public policies. A qualitative and quantitative approach and hermeneutic method were used in a study on the role of the school manager. It brings discussion, analysis and presentation of the results obtained, through the Data Collection Instruments - ICD, defining in the participants' view what it means to be a democratic and participatory management, pointing out the role of the school manager and his contribution to improving education. As a result, it is concluded that in effective leadership, it is necessary for the manager to know the theories, practices and skills. In this sense, in participatory management within the school environment, the manager has to seek strategies to effectively involve the participation of everyone involved in the educational process, and must not fail to relate theory to practice and reflect on the actions developed within the school.